Effectiveness and safety of narlaprevir in real clinical practice of chronic hepatitis C - V. V. Basina; S. E. Kalach; N. V. Tyurenkova; M. E. Semenova; E. Yu. Yushina; E. G. Gordievskaya; R. A. Ganchenko; Е. V. Esaulenko (Журнал инфектологии)
Objective: to analyze the efficacy and safety of using direct antiviral action drug narlaprevir/ritonavir in combination with the prolonged alpha-interferon and ribavirin drugs in the conditions of day-time hospitals of St. Petersburg and. Novgorod.Materials and methods: The study included. 35 patients with CHC of the 1st genotype. For treating these patients, a three-component regimen was used, which included the use of narlaprevir/ritonavir in combination, with peg-interferon and ribavirin.Results: among all patients included, in the study, a sustained, virological response was noted, in 85,7%. Early virological response was observed, in 91,3% cases. The recurrence rate was observed, in 10% patients. In 3 patients, therapy was interrupted, for the following reasons: due to inefficiency, the development of serious adverse events, and on its own initiative.Conclusion: the data obtained, demonstrate high, virological and. clinical efficacy and. safety of narlaprevir in combination with peg-interferon and ribavirin, in the treatment of chronic viral hepatitis C.